(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Lake Garda is located in Insubria region, that is known for being the most populated and industrialized area of Italy (Camusso et al., 2001). Therefore, the Lake water, and also the fish species present, could be affected by environmental contamination. European eel (Anguilla anguilla) are considered as suitable matrix for biomonitoring environmental contaminants in European water (Belpaire et al., 2007), being widespread in many European waters and highly contaminated by lipophilic compounds, due to the high lipid content (up to 40%) (Larsson et al., 1991). Moreover, eel is an edible species (its farming currently supplies approximately 45,000 tons/year) (Nielsen et al., 2008), so it also represents a public health issue. Based on these considerations, the aim of this study was to evaluate the occurrence of fourteen organochlorine pesticides (OCs) in forty-five eels (Anguilla anguilla) from Lake Garda, using Accelerated Solvent Extraction (ASE) procedure for the analytes extraction and Gas chromatography coupled with Tandem Mass Spectrometry (GC-MS/MS) for the analysis of OCs. GC-MS/MS analysis was developed and validated according to the SANTE/11945/2015 guidelines. Uncontaminated eel sample (previously checked for the presence of OCs and considered blank with a concentration of compounds < Limit of Detection) were used for all procedure’s optimization steps. For all the OCs analysed, satisfactory results were achieved. Regarding eel samples, several pesticides were detected, but DDTs (DDT and its metabolites) were found with the highest prevalence (92 %). The concentration rage was from not detected (n.d.) to 19000 ng g-1. Although DDTs levels in the environment are declining (Albaiges et al., 2011), they continue to bioaccumulate in tissues of human and animal and biomagnify in food chains.